АЛГОРИТМ ДОДАТКОВОГО КРИПТОГРАФІЧНОГО ЗАХИСТУ ГОЛОСОВИХ ДАНИХ - Гончарова, Сабіна Володимирівна; Могилевич, Д. І. (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2016)
Additional cryptographic algorithm protection of voice data This article describes the algorithm additional cryptographic protection of voice data in mobile network. The results of testing pseudo-random pattern generator are presented.